Serum Proteins in Allopatric and Sympatric Populations of Leptodactylus ocellatus and L. chaquensi - Cei, José Miguel Alfredo María (1961)
Leptodactylus ocellatus and L. chaquensis, two closely related species of Argentine anurans, were compared by an electrophoretic study of the serum protein patterns. Significant differences were obtained between the two species, both in the comparison of allopatric as well as sympatric populations.